Self-presentation of Female Stand-up Comedian on Instagram Account @aciresti - sofia aunul; Fitrie Handayani (Universitas Multimedia Nusantara, 2022)
The phenomenon of communication through social media is common as a result of the development of communication technology. By using an interpersonal communication theory approach, in this case the concept of self-presentation is used to find out how a female stand-up comedian presents herself on her Instagram account @aciresti and her self-presentation strategy. This research uses a qualitative approach with a case study method where primary data collection is conducted by interviewing the account owner—Aci Resti and also her followers as a form of triangulation of sources and secondary data is carried out by conducting literature studies and observing Instagram accounts. Aci Resti's self-presentation in her Instagram account shows a dynamic and hardworking female comedian and builds female characters who can compete in the stand-up comedy industry. The self-presentation strategy is ingratiation that is an attempt to make other people like her, while self-enhancement is shown that her abilities can be respected by others.